Therapeutic advantage of converting enzyme inhibitors in arresting progressive renal disease associated with systemic hypertension in the rat. - Anderson, S (1986)
Micropuncture and morphologic studies were performed in six groups of male Munich-Wistar rats after removal of the right kidney and segmental infarction of two-thirds of the left kidney. Groups 1 and 4 received no specific therapy. Groups 2 and 5 were treated with the angiotensin I-converting enzyme inhibitor, enalapril, 50 mg/liter, in the drinking water. Groups 3 and 6 were treated with reserpine (5 mg/liter), hydralazine (80 mg/liter), and hydrochlorothiazide (25 mg/liter). All rats were fed standard chow. Groups 1-3 underwent micropuncture study 4 wk after renal ablation. Untreated group 1 rats exhibited systemic hypertension and elevation of the single nephron glomerular filtration rate (SNGFR) due to high average values for the mean glomerular transcapillary hydraulic pressure gradient (delta P) and glomerular plasma flow rate (QA). In group 2 rats, treatment with enalapril prevented systemic hypertension and maintained delta P at near-normal levels without significant reduction in SNGFR and QA. In contrast, triple drug therapy normalized systemic hypertension, but failed to lower delta P in group 3 rats. Groups 4-6 were followed for 12 wk after renal ablation. Untreated group 4 rats demonstrated continuous systemic hypertension, progressive proteinuria, and glomerular structural lesions, including mesangial expansion and frequent areas of segmental sclerosis. In group 5 rats, treatment with enalapril maintained systemic blood pressure at normal levels over the 12-wk period and dramatically limited the development of proteinuria and glomerular lesions. Despite equivalent systemic blood pressure control in group 6 rats, failure of triple drug therapy to control glomerular hypertension was associated with progressive proteinuria and glomerular lesions comparable to those seen in untreated group 4 rats. Thus, unless glomerular capillary hypertension is corrected, control of systemic blood pressure is insufficient to prevent progressive renal injury in rats with reduced renal mass.